Bias and Representation: a Value Analysis in Republika Online Political Reporting - Rahmat Basit; Zamzani, Zamzani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This research aims to analyze the construction of relational values in political news published by Republika online media, focusing on identifying linguistic markers of relational values, examining how they construct bias and representation of political actors, and explaining their ideological function in shaping public perception. The analysis employs Norman Fairclough’s Critical Discourse Analysis (CDA), with relational values in vocabulary selection as the central focus at the textual level. Methodologically, this study adopts a descriptive qualitative approach, with data consisting of political news articles published by Republika between December 2023 and January 2024, collected through reading and note-taking techniques, then reduced, coded, and classified into four relational value categories (trust, respect, cooperation, and commitment). The findings indicate that vocabulary choices systematically construct political actors’ images: trust is represented through lexical items that reinforce credibility; respect emerges through honorifics and naming strategies that strengthen legitimacy; cooperation is conveyed through lexical choices emphasizing synergy; and commitment appears through expressions of promises and future-oriented political intentions. These results affirm that vocabulary selection in media texts is not neutral but carries ideological functions that shape political representation and readers’ interpretive orientation. Therefore, this research offers conceptual and empirical contributions to language and political discourse studies and reinforces the urgency of critical media literacy in the public sphere.